Penguatan Strategi Branding B2B (Business-to-Business) pada Zamora Collection Group - Ramadhani, Laila ‘Izza; Ningrum, Risma Widya; Oktaviyani, Tri; Fika’, Suciana Laili; Zahrotunnisa, Syifa Aulia; Irsyad, M. Ubaidillah; Fadilla, Leli; Syahira, Tata; Permatasari, Vina Septiana (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This community service activity aims to strengthen the B2B (business-to-business) branding strategy at Zamora Collection Group in order to increase competitiveness and product sales. The method used is the Participatory Action Research (PAR) approach, involving the Zamora Collection Group team in the design, implementation, and evaluation process of branding strategies. Community service steps include brand identity analysis, communication message adjustment, digital channel optimization, and improving team capabilities in B2B presentations and negotiations. The results of the activity showed an increase in brand awareness among business partners and the growth of strategic cooperation networks. The digital content produced managed to attract the attention of potential partners, while the team's capabilities in business communication showed significant improvements. Through a more targeted branding approach, Zamora Collection Group was able to strengthen its position as a provider of superior products in the B2B market.